Engineered soluble ACE2 receptor: Responding to change with change - Li, Guangyao; Qian, Kewen; Zhang, Shuyi; Fu, Wenyan; Zhao, Jian; Lei, Changhai; Hu, Shi (Frontiers in Immunology, 2023)
SARS coronavirus 2 (SARS-CoV-2) invades the human body by binding to major receptors such as ACE2 via its S-spike protein, so the interaction of receptor-binding sites has been a hot topic in the development of coronavirus drugs. At present, the clinical progress in monoclonal antibody therapy that occurred early in the pandemic is gradually showing signs of slowing. While recombinant soluble ACE2, as an alternative therapy, has been modified by many engineering methods, both the safety and functional aspects are approaching maturity, and this therapy shows great potential for broadly neutralizing coronaviruses, but its progress in clinical development remains stalled. Therefore, there are still several key problems to be considered and solved for recombinant soluble ACE2 to be approved as a clinical treatment as soon as possible.